Integrating Science, Technology, Engineering, and Mathematics in Digital Learning: The Effectiveness of an E-Module on Ecosystem Material in Secondary Schools - Mona Kristina Simatupang; Suryanti Suryanti; Iffa Ichwani Putri; Siti Robiah; Nurul Fauziah (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
The integration of the Science, Technology, Engineering, and Mathematics (STEM) approach into digital learning has the potential to enhance the quality of biology instruction by providing contextual, interactive, and problem-oriented learning experiences. Although previous studies have developed STEM-integrated e-modules with high validity and practicality, empirical evidence regarding their effectiveness in improving learning outcomes through comparisons between instructional groups remains limited. This study aimed to examine the effectiveness and practicality of a STEM-integrated e-module on ecosystem topics for tenth-grade students at SMAN 2 Pekanbaru. A quasi-experimental method with a Nonequivalent Control Group Design was employed, involving 88 students, comprising 44 students in the experimental class and 44 students in the control class. Data were collected through a learning achievement test and practicality questionnaires completed by teachers and students. The data were analyzed using the Mann–Whitney test, normalized gain (N-Gain), and effect size (r). The results revealed a significant difference in learning outcomes between the experimental and control classes (p < 0.001). The experimental class achieved a higher mean N-Gain (0.564) than the control class (0.334), with an effect size of 0.39, indicating a medium practical effect. The practicality evaluation also showed highly practical results, with scores of 86% from teachers and 88% from students. These findings indicate that the STEM-integrated e-module is effective in improving students' learning outcomes while also being highly practical for biology instruction at the secondary school level.